Workplace violence in Family Health Units: A study of mixed methods Violência no trabalho em saúde da família: Estudo de métodos mistos - Sturbelle I.C.S. (2019)
© 2019 Departamento de Enfermagem/Universidade Federal de Sao Paulo. All rights reserved.Objective: To verify the prevalence of workplace violence in Family Health Units, characterize the victims and know the implications of conditions and organization of work in workers exposure. Methods: A mixed study of the concomitant type. The quantitative stage included a sample of 106 health professionals from 17 Family Health Units who answered questions about sociodemographic data and the Survey Questionnaire Workplace Violence in the Health Sector. At the qualitative stage, 18 violence victims workers were intentionally selected to respond to the semi-structured interview. Quantitative findings were subjected to descriptive and analytical statistics, and qualitative data to thematic analysis. Results: About 69.8% of the workers were exposed to violence, with the main victims being younger workers and the nursing staff (p=0.047). Violence was also associated with a worse assessment of relationships with colleagues (p=0.003) and managers (p=0.008). The interviewees attributed to the reception of the unit the space of greatest risk of aggression. The lack of resources, absence of a doctor in the unit and its location in areas of trafficking were aspects related to the exposure of professionals to violence. Conclusion: Violence has proved prevalent in work in family health units and improvements in structure, human and material resources as well as public safety are needed to control and prevent worker aggression.